Characterization and Identification of Single Nucleotide Polymorphism Within the IGF‐1R Gene Associated with Growth Traits of Odontobutis potamophila. Issue 2 (14th January 2018) - Zhang, Hongye; Zhao, Cheng; Yin, Shaowu; Li, Zecheng; Cao, Quanquan; Li, Xinru; Xie, Wanli; Zhang, Jiajia; Zhu, Wenxu; Wang, Dan
Abstract: IGF‐1R plays a critical role in many physiological activities, such as development, growth, metabolism, and reproduction. Identification of genetic markers in the IGF‐1R gene significantly associated with important growth traits of Odontobutis potamophila may accelerate genetic improvement. In this study, we characterized the cDNA sequence of the IGF‐1R gene of O. potamophila, and our data revealed that IGF‐1R contained an open reading frame of 1650 bp, encoding a polypeptide of 549 amino acids (aa). Quantitative real‐time polymerase chain reaction demonstrated that IGF‐1R was ubiquitously expressed in all tested tissues, and the most predominant expression of IGF‐1R was detected in gonad. Moreover, IGF‐1R was expressed at different developmental stages from embryo to larva, and its highest expression level was found at the morula stage. In addition, we identified three single nucleotide polymorphisms (SNPs; 1777T>C, 1704G>A, and 1208G>A) within IGF‐1R locus and found that one SNP (1208G>A) was significantly associated with important growth traits of O. potamophila . Results showed that the overall length, body length, trunk width, caudal peduncle length, body weight, and body width in fish with AG genotype were significantly greater compared with those with GG genotype ( P < 0.05). However, the other two SNPs (1777T>C and 1704G>A) did not show significant associations with any growth traits. Therefore, SNPs within the IGF‐1R locus could be used as a selection criterion to improve growth traits of O. potamophila .